1,25-dihydroxyvitamin D3 improves non-alcoholic steatohepatitis phenotype in a diet-induced rat model - Mei Liu; Xiang-Zhun Song; Liu Yang; Yu-Hui Fang; Liu Lan; Jing-Shu Cui; Xiao-Chen Lu; Hai-Yang Zhu; Lin-Hu Quan; Hong-Mei Han (Frontiers in Endocrinology)
We studied the potential protective effects of 1,25-dihydroxyvitamin D3 (1,25 VD3) supplementation on liver damage induced by a choline-deficient (CD) diet in rats, where impaired liver function leads to decreased 25-hydroxyvitamin D3 levels, the precursor for the active 1,25 VD3. The CD diet reduced serum 25 VD3 levels and increased liver enzymes, indicative of liver damage. Conversely, 1,25 VD3 supplementation alleviated liver damage, reducing liver enzymes and improving histopathological features characteristic of non-alcoholic steatohepatitis (NASH). Oxidative stress and inflammation were mitigated by 1,25 VD3, as evidenced by decreased malondialdehyde and nuclear factor kappa B (NF-κB) expression, and increased total antioxidant capacity (TAOC). 1,25 VD3 also enhanced fatty acid metabolism by increasing peroxisome proliferator-activated receptor alpha (PPARα) and carnitine palmitoyltransferase-1 (CPT-1) expression, promoting lipid transport and oxidation. Additionally, 1,25 VD3 supplementation modulated inflammation by increasing PPARγ expression, reducing NF-κB expression, and decreasing pro-inflammatory cytokines (TNF-α, IL-1β). Anti-inflammatory cytokines (IL-10, IL-4) were increased, and macrophage polarization was shifted towards an anti-inflammatory M2 phenotype. Moreover, 1,25 VD3 upregulated CYP2J3, a cytochrome P450 epoxygenase that converts arachidonic acid to anti-inflammatory epoxyeicosatrienoic acids (EETs) and decreased soluble epoxide hydrolase activity, likely contributing to increased EET levels. Correlation studies revealed positive associations between 1,25 VD3 supplementation, CYP2J3 expression, EETs, as well as negative correlations with NF-κB and TNF-α. PPARα expression positively correlated with TAOC and CPT-1, while PPARγ expression negatively correlated with inflammatory markers. These findings demonstrate the therapeutic potential of 1,25 VD3 in alleviating NASH through regulation of fatty acid metabolism, inflammation, and oxidative stress.